PENGARUH POSISI CONDONG KE DEPAN (CKD) DENGAN PURSED LIPS BREATHING (PLB) TERHADAP PENINGKATAN KONDISI PERNAFASAN PASIEN PENYAKIT PARU OBSTRUKTIF KRONIK (PPOK) - Suci Khasanah; Madyo Maryoto (Viva Medika, 2015)
Background: As care provider, the nurses providing nursing care service to helpimprove respiratory function COPD patients.Objectives: To investigate the influence of CKD position and CKD positiontoward PLB to increased respiratory Functions of COPD patients.Methods: An experimental study was design randomized control trial pre-post testwith control group technique among 33 COPD patients. Result: This study found that there is not significant difference between beforeintervention group and after intervention group with the p-value > Î±. Conclusion: The CKD position and PLB therapy are more effective than CKDposision or semi-flower to decrease the problem of dipsnea. Three-day-treatmentof CKD posision and PLB done continually is as effective as the CKD position ofsingle treatment to increase SaO2 and to increase RR respectively than that withsemi fowler position. keywords: RR, SaO2, Problem of dipnea, Quantity exhaled air, COPD, PLB, theposition of CKD